Caracterización de la flora arbórea en la recarga hídrica de la comunidad “La Mariposa” en la microcuenca del carrizal - Cedeño Falcones, Cristhian Yoel (2019)
The research aimed to characterize the tree flora of the La Mariposa community of the Carrizal River Basin. In order to know the biodiversity and importance of tree species, in this way the forested areas of the community were identified through the use of the cartographic technique, likewise two transects of 50x50m each were established, within the forested area. In addition, dasometric variables were recorded in all individuals identified with the diameter at chest height or a height of 1.30m from the ground. It was possible to identify 16 families and 22 species within the transects made. Where the species Saman (Samanea saman), Spanish (Maclura tintoria), linden (Tilia sp.) And caraca (Enterolobium cyclocarpum) are native to the community. Likewise, it determined that the Samanea saman species with 30.57% and Guaiacum officinale 23.78% have a higher percentage of the importance value index within the community, verifying with the scientific literature the environmental benefit that contributes both within their ecosystem and to Water recharge protection. In addition, a survey was carried out to determine the degree of knowledge they possess about the importance of tree flora, through the results of the same, a strategy for the conservation of forest areas and the sustainable use of these areas was proposed.